Age-related differences in neural recruitment during the use of cognitive reappraisal and selective attention as emotion regulation strategies - Allard, Eric S.; Kensinger, Elizabeth A. (Frontiers in Psychology, 2014)
The present study examined age differences in the timing and neural recruitment within lateral and medial PFC while younger and older adults hedonically regulated their responses to unpleasant film clips. When analyses focused on activity during the emotional peak of the film clip (the most emotionally salient portion of the film), several age differences emerged. When comparing regulation to passive viewing (combined effects of selective attention and reappraisal) younger adults showed greater regulation related activity in lateral PFC (DLPFC, VLPFC, OFC) and medial PFC (ACC) while older adults showed greater activation within a region DLPFC. When assessing distinct effects of the regulation conditions, an ANOVA revealed a significant Age X Regulation Condition interaction within bilateral DLPFC and ACC; older adults but not young adults showed greater recruitment within these regions for reappraisal than selective attention. When examining activity at the onset of the film clip and at its emotional peak, the timing of reappraisal-related activity within VLPFC differed between age groups: Younger adults showed greater activity at film onset while older adults showed heightened activity during the peak. Our results suggest that older adults rely more heavily on PFC recruitment when engaging cognitively demanding reappraisal strategies while PFC-mediated regulation might not be as task-specific for younger adults. Older adults’ greater reliance on cognitive control processing during emotion regulation may also be reflected in the time needed to implement these strategies.